Temperature Dependence of the New Calibration Infrastructure for Impedance Metrology - Marian Kampik; Krzysztof Musioł; Ryszard Rybski; Janusz Kaczmarek; Mirosław Kozioł; Maciej Koszarny; Adam Ziółek; Jolanta Jursza; Paweł Zawadzki (Energies)
This paper addresses issues relating to the temperature stability of impedance infrastructure used for the realization of impedance units and the calibration of measuring instruments. A description of the new infrastructure for impedance metrology recently developed in Poland is provided. We present the results of measurements of temperature coefficients for four-port resistance standards and two-port capacitors used in the permuting capacitor device. We also report the results of stability tests of the recently developed temperature-controlled capacitance set. The results demonstrate excellent temperature stability for the impedance components and serve as an important source of information for selecting environmental conditions during comparisons and routine calibration.